Heat- or light-induced acylarylation of unactivated alkenes towards 3-(α-acyl) indolines. Issue 29 (14th July 2020) - Li, Yanni; Ying, Fengyuan; Fu, Tingfeng; Yang, Ruihan; Dong, Ying; Lin, Liqing; Han, Yinghui; Liang, Deqiang; Long, Xianhao
Abstract : A heat- or photoredox/iron dual catalysis-enabled rare example of radical acylation across unactivated alkenes with aldehydes. Abstract : A heat- or photoredox/iron dual catalysis-enabled dehydrogenative acylarylation of N -allyl anilines leading to 2-substituted 3-(α-acyl) indolines with a quaternary stereogenic center is presented, with unactivated alkenic bonds as radical acceptors and simple aldehydes as radical precursors. This reaction features high yields, a broad substrate scope, and a great exo selectivity, and gram-scale syntheses could be readily carried out.